2011
DOI: 10.1109/led.2011.2169040
|View full text |Cite
|
Sign up to set email alerts
|

Edge Effects in Self-Heating-Related Instabilities in p-Channel Polycrystalline-Silicon Thin-Film Transistors

Abstract: Self-heating-related instabilities have been investigated in p-channel polycrystalline-silicon thin-film transistor, showing an anomalous transconductance (g m ) increase. The g m increase is a fingerprint of edge effects, resulting from a buildup of positive trapped charge in the gate oxide at the channel edges. This was confirmed by the annihilation of such positive charges obtained by sequential hot-carrier bias-stress experiments. From the analysis of the edge effects in devices with different channel leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…On the other hand, since a part of SH degradation occurs at GBs, the less GB N t of unstressed BG ploy-Si TFTs may also contribute to the alleviation of SH degradation. In addition, it is also observed that for normal poly-Si TFTs, as clearly shown in the inset, longer L brings more severe SH degradation at the same p. This is partly attributed to the geometric effect [19], [20], [22] and partly attributed to the higher |E ox | that normal poly-Si TFT with L = 12 μm suffers from.…”
Section: B Self-heatingmentioning
confidence: 75%
See 1 more Smart Citation
“…On the other hand, since a part of SH degradation occurs at GBs, the less GB N t of unstressed BG ploy-Si TFTs may also contribute to the alleviation of SH degradation. In addition, it is also observed that for normal poly-Si TFTs, as clearly shown in the inset, longer L brings more severe SH degradation at the same p. This is partly attributed to the geometric effect [19], [20], [22] and partly attributed to the higher |E ox | that normal poly-Si TFT with L = 12 μm suffers from.…”
Section: B Self-heatingmentioning
confidence: 75%
“…The SH degradation depends upon Joule heating generated by high-stress power [15]- [20] and upon E ox generated by stress V g [22]. Therefore, to make the SH degradation comparison between normal poly-Si TFTs and BG poly-Si TFTs more fair, the stress power density p, which equals to stress power divided by the area of the channel, and E ox are employed for the SH discussion.…”
Section: B Self-heatingmentioning
confidence: 99%